A systematic literature review of AI in the sharing economy. Issue 3 (3rd July 2022) - Chen, Ying; Prentice, Catherine; Weaven, Scott; Hsiao, Aaron
ABSTRACT: Although artificial intelligence (AI) has been adopted in sharing economy platforms, few studies have investigated this phenomenon in this context. Consequently, there is no thorough overview of how AI has been used in the sharing economy. To address this research gap, a systematic literature review was performed for this paper. This method can be useful for the exploration of new and emerging trends within disciplines and allows boundaries to be mapped on what is known thereby identifying gaps on what is yet to be known. After screening, 28 English journal articles were selected in a qualitative synthesis. Results show AI can help the sharing economy platforms by enhancing trust, matching assets, and understanding participants' preferences and attitudes. Based on these findings, potential directions are established. The current study will contribute to both the sharing economy and AI literature, and the results may help practitioners and academia to achieve a greater understanding of this topic.